2019
DOI: 10.1017/s0267190519000011
|View full text |Cite
|
Sign up to set email alerts
|

Reframing Technology's Role in Language Teaching: A Retrospective Report

Abstract: As the field of applied linguistics ponders and even embraces the myriad roles technology affords language education, we frame this critical report within the context of the Modern Language Association's 2007 report, along with earlier state-of-the-field Annual Review of Applied Linguistics (ARAL) pieces (e.g., Blake, 2007; 2011) to consider not only where we've come from but also, crucially, where the field is headed. This article begins with an overview of the field, examining the role of technology and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 58 publications
1
8
0
1
Order By: Relevance
“…For example, the result of Trinder’s (2016) study shows that while not denying the advantages of blending learning, students still have a stronger desire for face-to-face language teaching. A similar result can also be obtained in Lomicka and Lord (2019), who show that 77.29% of students tend to use completely or mainly face-to-face teaching, while 59.72% of teachers prefer that method, and that the rest of the student group and the teacher group prefer the 50:50 method consisting of online plus face-to-face teaching, with no student or teacher preferring the completely online teaching. Studies of such a kind indicate that both students and teachers are aware of the importance of face-to-face interaction in language teaching and learning, and meanwhile they also reflect the differences between language teaching and the teaching of other disciplines, which also confirm the view of socio-cultural theory and interactionism theory.…”
Section: Rethinking the Perceptions Of Fcsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, the result of Trinder’s (2016) study shows that while not denying the advantages of blending learning, students still have a stronger desire for face-to-face language teaching. A similar result can also be obtained in Lomicka and Lord (2019), who show that 77.29% of students tend to use completely or mainly face-to-face teaching, while 59.72% of teachers prefer that method, and that the rest of the student group and the teacher group prefer the 50:50 method consisting of online plus face-to-face teaching, with no student or teacher preferring the completely online teaching. Studies of such a kind indicate that both students and teachers are aware of the importance of face-to-face interaction in language teaching and learning, and meanwhile they also reflect the differences between language teaching and the teaching of other disciplines, which also confirm the view of socio-cultural theory and interactionism theory.…”
Section: Rethinking the Perceptions Of Fcsupporting
confidence: 79%
“…Por ejemplo, los resultados obtenidos por Trinder (2016) en su estudio demuestran que, aunque no se niegan las ventajas de un aprendizaje mixto, los estudiantes siguen expresando su deseo de disponer de una enseñanza presencial. También se observaron resultados similares en el estudio de Lomicka y Lord (2019), que demostraron que un 77.29% de los estudiantes tendían hacia una enseñanza total o principalmente presencial, y que un 59.72% de los docentes preferían también esta modalidad, mientras que el resto de los estudiantes y docentes preferían un método mixto al 50% de educación en línea y presencial, y ninguno de ellos expresó preferencia por una enseñanza totalmente en línea. Estudios de este tipo indican que tanto el estudiantado como el profesorado son conscientes de la importancia de la interacción personal en la educación de lenguas extranjeras, y reflejan también las diferencias entre la enseñanza y el aprendizaje de lenguas y otras disciplinas, lo que confirma la perspectiva de la teoría sociocultural y del interaccionismo.…”
Section: Reevaluación De Las Percepciones Del Aiunclassified
“…AR applications, on the other hand, enhance language learning by overlaying digital information, such as translations or subtitles, onto the physical world. These technologies create a sense of presence and make language acquisition more engaging and memorable [14].…”
Section: Mobile Applications and Language Learning Toolsmentioning
confidence: 99%
“…Hanson-Smith (2006) promotes the use of communities of practice (CoPs) as a potential solution. Lomicka and Lord (2019) echo the call others have made to integrate CALL teacher preparation within general language teacher preparation. However, research has observed that most of these programs present insufficient forms of training, which leave many graduates dependent upon alternative forms of professional development if they are to learn anything about CALL (Kessler & Hubbard, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…For years, researchers have suggested that preparation for CALL in teacher education is lacking. As a result, CALL practice continues to be superficial and not meaningfully integrated into instructional practice (Kessler, 2006;Lomicka & Lord, 2019). In spite of the obvious demand for CALL-related skills across the language teaching profession, language teachers do not receive adequate preparation, and what they do receive is often inappropriate, leaving future professionals to rely on learning about these topics independently or through a mix of short-term professional development opportunities (Kessler, 2006).…”
Section: Introductionmentioning
confidence: 99%